AGRICULTURAL TOURISM MANAGEMENT - Kerwei, Yang (Asia Pacific Journal of Religions and Cultures, 2025)
In the past, it was believed that tourism had an impact on the environment, society, and culture. In order to lessen the effects, communities started to adapt more through eco-tourism, health-oriented tourism, and agricultural-oriented tourism. Agricultural tourism is a combination of agricultural activities, community ways of life, and cultivating awareness about preserving community resources along with tourism. The development of agricultural tourism destinations is therefore a new option for both Thai and foreign tourists. The agricultural tourism management mechanism requires community members to participate in the development of agricultural tourism destinations. Doing activities to learn together through experiences, focusing on tourists and people in the community, including developing tourist attractions to meet tourism standards to be ready to accommodate tourists. There is marketing, promotion, and cooperation to conserve the environment and achieve sustainability. This is considered a way of developing sustainable agritourism. The agritourism management mechanism is therefore management, starting from the process of planning, organizing, leading, and controlling in terms of participation. Management and public relations media to increase tourists coming to travel in the community. and generate income for the community.